2018
DOI: 10.1089/neu.2017.5434
|View full text |Cite
|
Sign up to set email alerts
|

Rho Inhibitor VX-210 in Acute Traumatic Subaxial Cervical Spinal Cord Injury: Design of the SPinal Cord Injury Rho INhibition InvestiGation (SPRING) Clinical Trial

Abstract: Traumatic spinal cord injury (SCI) is associated with a lifetime of disability stemming from loss of motor, sensory, and autonomic functions; these losses, along with increased comorbid sequelae, negatively impact health outcomes and quality of life. Early decompression surgery post-SCI can enhance patient outcomes, but does not directly facilitate neural repair and regeneration. Currently, there are no U.S. Food and Drug Administration–approved pharmacological therapies to augment motor function and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 42 publications
0
53
0
1
Order By: Relevance
“…Because of the promising results of phase I/IIa clinical trial, VX-210 was moved to a phase IIb/III SPRING (SCI Rho inhibition investigation) trial for acute traumatic cervical SCI (NCT02669849). The major goal of this randomized, double-blind, placebo-controlled trial was to evaluate its safety and efficacy in promoting functional recovery by Rho inhibition (Fehlings et al, 2018 ). However, this trial was terminated by Vertex probably because of lack of efficacy after an interim analysis.…”
Section: Cspg Downstream Signals Are Therapeutic Targets For Cns Injumentioning
confidence: 99%
“…Because of the promising results of phase I/IIa clinical trial, VX-210 was moved to a phase IIb/III SPRING (SCI Rho inhibition investigation) trial for acute traumatic cervical SCI (NCT02669849). The major goal of this randomized, double-blind, placebo-controlled trial was to evaluate its safety and efficacy in promoting functional recovery by Rho inhibition (Fehlings et al, 2018 ). However, this trial was terminated by Vertex probably because of lack of efficacy after an interim analysis.…”
Section: Cspg Downstream Signals Are Therapeutic Targets For Cns Injumentioning
confidence: 99%
“…This has been investigated in different animal models (Dubreuil et al, 2003 ; Boato et al, 2010 ; Loske et al, 2012 ). Moreover, systematic reviews and meta-analyses (Watzlawick et al, 2014 ), as well as clinical trials in humans, have subsequently confirmed these findings (McKerracher and Anderson, 2013 ; Fehlings et al, 2018 ).…”
Section: Introductionmentioning
confidence: 90%
“…Ihnen gemeinsam ist, dass ihr am detailliertesten untersuchter Wirkmechanismus nach zellulärer Internalisierung auf einer enzymatischen Inaktivierung von kleinen GTP-bindenden Proteinen der Rho-Familie (A, B und C) beruht [16]. Da, wie vorab erwähnt, insbesondere die Aktivierung von RhoA in der überwiegenden Mehrzahl der untersuchten Modellsysteme zur neuronalen Regeneration hemmend auf das Auswachsen von Axonen wirkt, stellt eine Hemmung der Hemmung ein attraktives Ziel zur Förderung des neuronalen (Wieder-)Auswachsens dar, was bereits Eingang in klinische Studien im Zusammenhang mit der Querschnittslähmung gefunden hat [17].…”
Section: Direkte Hemmung Rhoa-abhängiger Signalwege: Inaktivierung Duunclassified